Oil absorption expansion thermoplastic elastomer composition and preparation method thereof
By using oil-absorbing and expanding thermoplastic elastomer composition in the oil-absorbing and swelling sheath material, the network structure is formed by using micro-phase separation and cross-linking reactions, the problem of insufficient oil-resistant decomposition ability of the material when immersed in crude oil for a long time is solved, and the efficient oil-absorbing and stable expansion effect of the material is achieved.
Patent Information
- Application Number
- CN202510436546.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-09
- Publication Date
- 2025-05-09
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing oil-absorbing and swelling sheath materials are difficult to maintain their resistance to oil decomposition when immersed in crude oil for a long time, resulting in decomposition.
Using an oil-absorbing expanded thermoplastic elastomer composition, including ethylene propylene ternary rubber, polypropylene, peroxide or phenolic resin composition, oil-absorbing components, slip agents, flow regulators and anti-aging agents, a network structure is formed through micro-phase separation and cross-linking reactions to enhance the anti-oil decomposition ability of the material.
This material is soaked at room temperature for 24 hours and only slightly decomposes or even does not decompose. It has a high oil absorption capacity and expansion degree, and is suitable for oil-sensitive optical cables.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of polymer materials, and in particular to an oil-swellable thermoplastic elastomer composition and a preparation method thereof. Background Art
[0002] At present, the monitoring technologies used by the safety operation and maintenance management system include video monitoring, gas sensors, oil-sensing optical cables, and manual patrols. The oil-sensing optical cables are composed of sensing optical fibers, elastic layers, and oil-absorbing and swelling sheaths from the inside to the outside. The oil-absorbing and swelling sheaths are used to deform when in contact with oil.
[0003] Sometimes, due to the influence of the environment, it is difficult for technicians to quickly reach the oil leak point. At this time, it is necessary to improve the oil absorption and swelling sheath material's ability to resist oil decomposition, so that it can be immersed in crude oil for a long time without decomposition. Summary of the invention
[0004] In order to solve the problem that the oil-absorbing and swelling sheath material can have a high ability to resist oil decomposition, the present application provides an oil-absorbing and swelling thermoplastic elastomer composition, which can be immersed in oil for 24 hours at room temperature with only slight decomposition or even no decomposition. At the same time, the oil-absorbing and swelling thermoplastic elastomer composition of the present application has a high oil absorption capacity, a large degree of swelling after oil absorption, and can be better applied to oil-sensitive optical cables.
[0005] In a first aspect, the present application provides an oil-swellable thermoplastic elastomer composition, which adopts the following technical solution: An oil-swellable thermoplastic elastomer composition comprises the following components in parts by weight: 25 parts of EPDM rubber, 15-30 parts of polypropylene, a peroxide or phenolic resin composition, 40-60 parts of an oil-absorbing component, 0.5-2 parts of a lubricant, 1-3 parts of a flow regulator, and 1-2 parts of an anti-aging agent; The oil absorption component includes at least one of Kraton G1701M, Kraton G1702, and SEPTON 1020; The peroxide comprises at least one of DCP and TAIC; the weight portion of the peroxide is 1-2 parts; The phenolic resin composition is a mixture of phenolic resin, stannous chloride and zinc oxide; the weight portion of the phenolic resin composition is 1.5-3 parts.
[0006] By adopting the above technical solution, the oil absorption component (Kraton G1701M, Kraton G1702, SEPTON 1020) is a diblock copolymer of styrene and rubber. This special block structure allows the copolymer to undergo microphase separation during the curing film formation process, forming micro-regions with different compositions and properties. Due to the microphase separation characteristics of the block copolymer, many tiny pores and channels are formed inside it. These pores and channels provide space for the penetration and adsorption of oil molecules. When the oil molecules contact the surface of the block copolymer, they gradually penetrate into the material along these pores and channels. The rubber segment has good lipophilicity and can interact with the oil molecules. This interaction makes it easier for the oil molecules to be adsorbed and retained inside the block copolymer.
[0007] Peroxides form a stable CC network structure by initiating a crosslinking reaction between the molecular chains of the elastomer composition, thereby strengthening the network structure of the elastomer. The phenolic resin composition forms a network structure with the molecular chains of the elastomer composition by physical or chemical crosslinking. Peroxides and phenolic resins use different crosslinking methods to produce more network structures in the elastomer, so that the elastomer can still maintain a certain mechanical strength after oil absorption and avoid being dissolved.
[0008] The present application uses the oil absorption component (Kraton G1701M, Kraton G1702, SEPTON 1020) to absorb a large amount of common oils by utilizing its own microphase separation characteristics; at the same time, the peroxide or phenolic resin composition utilizes different cross-linking methods to make the elastomer produce a large number of network structures, so that the elastomer can still maintain a certain mechanical strength after oil absorption and avoid being dissolved, so that the oil absorption and expansion thermoplastic elastomer composition can stably maintain the expansion state after oil absorption, and can be better applied to oil-sensitive optical cables.
[0009] Preferably, the phenolic resin includes at least one of SP1044, SP1045, SP1055, and SP1056.
[0010] Preferably, the phenolic resin is SP1056.
[0011] By adopting the above technical solution, SP1056 is a brominated thermo-reactive resin that contains more bromine components than other phenolic resins and therefore has a faster vulcanization speed. In oil-swellable thermoplastic elastomer compositions, a fast vulcanization speed helps improve production efficiency and ensures that the composition reaches a stable cross-linked state in a short time.
[0012] Preferably, the phenolic resin composition also includes stearic acid.
[0013] By adopting the above technical solution, the phenolic resin itself has a certain vulcanization effect, which can trigger a cross-linking reaction between the molecular chains of the elastomer composition under heating conditions. Zinc oxide, as an important catalyst in the vulcanization process, can reduce the activation energy of the vulcanization reaction, thereby accelerating the vulcanization reaction.
[0014] Stearic acid can react with zinc oxide to form a stable zinc stearate salt. This reaction not only consumes the active sites on the surface of zinc oxide, reduces the agglomeration between zinc oxide particles, but also improves the dispersibility of zinc oxide in the composition. More importantly, zinc stearate salt, as an active substance, can further promote the vulcanization reaction and accelerate the crosslinking between the molecular chains of the elastomer composition. By adding stearic acid, the vulcanization reaction can be carried out more fully, thereby increasing the crosslinking density of the composition, which helps to enhance the physical properties of the composition.
[0015] Preferably, the mass ratio of zinc oxide to stearic acid in the phenolic resin composition is 1:1-2.
[0016] By adopting the above technical scheme, if the mass ratio of stearic acid is too small, the amount of zinc stearate salt generated by its reaction with zinc oxide will not be enough to fully catalyze the vulcanization reaction. Stearic acid is a lipophilic substance, but the zinc stearate salt formed after it reacts with zinc oxide may have a certain oleophobicity. When the content of stearic acid is too much, the proportion of zinc stearate salt in the composition will also increase accordingly, which may form a relatively oleophobic barrier layer, hindering the penetration of oil molecules into the elastomer. Therefore, too much stearic acid will cause the penetration of oil into the elastomer to be weakened, thereby reducing the oil absorption effect.
[0017] Preferably, the peroxide is a mixture of DCP and TAIC.
[0018] By adopting the above technical solution, DCP (diisopropyl peroxide) and TAIC (triallyl isocyanurate) are selected as a mixture of peroxides. Compared with DCP and the other two auxiliary cross-linking agents, DCP and TAIC have better effects.
[0019] DCP and TAIC have a synergistic effect in the crosslinking reaction. DCP, as a commonly used peroxide crosslinking agent, can decompose under heating conditions to produce free radicals, initiating a crosslinking reaction between the molecular chains of the elastomer composition. TAIC, on the other hand, has multiple allyl functional groups, which can quickly participate in the crosslinking reaction in the presence of free radicals to form a tighter crosslinking network. Therefore, the mixed use of DCP and TAIC can significantly enhance the crosslinking effect and increase the crosslinking density of the composition. Compared with the use of DCP or TAIC alone, the mixture can reach the desired degree of crosslinking more quickly. This helps to shorten the production cycle and improve production efficiency.
[0020] Preferably, the mass ratio of DCP to TAIC in the mixture is 1:0.3-0.6.
[0021] By adopting the above technical solution, if the quality of TAIC is too low, the number of allyl functional groups it provides will be insufficient to fully react with the free radicals generated by the decomposition of DCP, resulting in an incomplete crosslinking reaction. This will reduce the crosslinking density of the composition, thereby affecting its physical properties and heat resistance.
[0022] If the mass of TAIC is too high, the mass of DCP will be relatively low. If the mass of DCP is low, the excess TAIC will not be able to further increase the degree of crosslinking, but will reduce the crosslinking density of the overall composition, thus affecting its oil absorption capacity.
[0023] Preferably, the oil absorption-swellable thermoplastic elastomer composition further comprises TPEE.
[0024] By adopting the above technical solution, the addition of TPEE (thermoplastic polyester elastomer) can make the composition accommodate more oil-absorbing components. TPEE itself has good elasticity and flexibility, which enables it to form an effective micropore or channel structure in the composition, which is conducive to the penetration and adsorption of oils. When the composition is exposed to an oil environment, the oil can quickly penetrate into these micropores or channels, thereby achieving an efficient oil absorption effect. TPEE has high mechanical strength and toughness, and can withstand the impact and extrusion of oil molecules on the material structure during the oil absorption process, thereby preventing the composition from being deformed or broken due to excessive oil absorption.
[0025] TPEE has excellent oil resistance and good anti-solubility to a variety of oils. After adding TPEE to the composition, the oil resistance of the composition can be significantly improved. Even if a large amount of oil-absorbing components are added to the composition, TPEE can effectively prevent the oil molecules from dissolving the composition matrix, thereby ensuring that the composition can maintain stable performance and shape during long-term use.
[0026] Preferably, the weight portion of TPEE is 1.5-3 parts.
[0027] By adopting the above technical solution, if the amount of TPEE is too small, the oil absorption capacity of the composition is not significantly improved. If the amount of TPEE is too large, the compatibility of TPEE and polypropylene is poor, which reduces the oil absorption capacity of the elastomer composition.
[0028] In a second aspect, the present application provides a method for preparing an oil-swellable thermoplastic elastomer composition, which adopts the following technical solution: A method for preparing an oil absorption-swellable thermoplastic elastomer composition, which is used to prepare the oil absorption-swellable thermoplastic elastomer composition, comprises the following steps: The polypropylene is divided into polypropylene A and polypropylene B, and the mass ratio of the polypropylene A to the polypropylene B is 1:0.7-1.1; S1: mixing the formulated amount of polypropylene A, EPDM rubber and flow regulator uniformly and then extruding to obtain a masterbatch; S2: uniformly mixing the formulated amount of peroxide or phenolic resin composition with the masterbatch and vulcanizing the mixture to obtain a sulfide; S3: uniformly mixing the formulated amount of polypropylene B, the oil absorption component, the lubricant and the anti-aging agent, and extruding and granulating them together with the sulfide to obtain an oil absorption and swelling thermoplastic elastomer composition.
[0029] In summary, this application has the following beneficial effects: 1. Since the present application uses the oil absorption component (Kraton G1701M, Kraton G1702, SEPTON 1020) to absorb a large amount of common oils by utilizing its own microphase separation characteristics; at the same time, the peroxide or phenolic resin composition uses different cross-linking methods to make the elastomer produce a large number of network structures, so that the elastomer can still maintain a certain mechanical strength after oil absorption and avoid being dissolved, so that the oil absorption expansion thermoplastic elastomer composition can stably maintain the expansion state after oil absorption, and can be better applied to oil-sensitive optical cables; 2. The stearic acid added to the phenolic resin composition of the present application can react with zinc oxide to form a stable zinc stearate salt, further promoting the vulcanization reaction and increasing the crosslinking density of the composition; 3. TPEE can also be added to the present application, which is beneficial to the penetration and adsorption of oils and can significantly improve the oil solubility resistance of the composition. DETAILED DESCRIPTION
[0030] The raw materials in this application include the following parts: Polypropylene: a commercially available product with CAS No. 9003-07-0 is used; EPDM rubber: commercially available products such as Mitsui Chemicals 3092, ExxonMobil Vistalon 5601, Dow Chemicals NORDEL 4760P, etc.; this application uses the commercially available product Mitsui Chemicals 3092 as an example; DCP: dicumyl peroxide, a commercial product with CAS number 80-43-3; TAIC: triallyl isocyanurate, a commercial product with CAS number 1025-15-6; TMPTMA: trimethylolpropane trimethacrylate, a commercial product with CAS number 3290-92-4; BMI: diphenylmethane bismaleimide, a commercial product with CAS number 13676-54-5; Phenolic resin: commercially available phenolic resin products with models of SP1044, SP1045, SP1055 and SP1056 are used; Stannous chloride: a commercially available product with CAS number 7772-99-8; Zinc oxide: a commercially available product with CAS number 1314-13-2; Stearic acid: a commercially available product with CAS number 57-11-4 is used; Lubricant: commercially available products such as silicones, fatty acids, fatty acid salts, and amides may be used; this application uses the commercially available silicone lubricant products of Hangzhou Kaijie Plastic Technology Co., Ltd. as an example; Flow regulator: commercially available products such as paraffin wax, polyethylene wax, olefin resin, etc. can be used; this application uses the commercially available product Huntsman APAO2180; Anti-aging agent: the thioether antioxidants used include dibutyl diacetate (DBTDL), diphenylthiourea (DPTT), etc. This application uses the commercially available product of dibutyl diacetate with CAS No. 14338-82-0 as an example; TPEE: thermoplastic polyester elastomer, using the commercially available product with the US DuPont brand number 5555HS; The present application is further described in detail below with reference to examples and comparative examples.
[0031] Example 1 A method for preparing an oil-swellable thermoplastic elastomer composition comprises the following steps: 23 kg of polypropylene is divided into 11 kg of polypropylene A and 12 kg of polypropylene B. The mass ratio of polypropylene A to polypropylene B is 1.09. In fact, the mass ratio of polypropylene A to polypropylene B can be in the range of 0.7-1.1.
[0032] S1: 11 kg of polypropylene A, 25 kg of EPDM rubber and 2 kg of flow regulator are mixed and extruded to obtain a masterbatch; S2: 2 kg of phenolic resin composition is mixed evenly with a masterbatch and then vulcanized to obtain a sulfide; the phenolic resin composition contains 1.4 kg of SP1056 phenolic resin, 0.3 kg of stannous chloride, and 0.3 kg of zinc oxide; S3: 12 kg of polypropylene B, 50 kg of Kraton G1701M, 1 kg of lubricant and 1 kg of anti-aging agent were mixed evenly, and extruded and granulated together with sulfide to obtain an oil-swellable thermoplastic elastomer composition.
[0033] Example 2-3 Example 2-3 Based on the preparation method of Example 1, the content of each component of the oil absorption-swellable thermoplastic elastomer composition was adjusted. The specific adjustments are shown in Table 1.
[0034] Comparative Example 1-2 Comparative Example 1 is based on the preparation method of Example 1, except that 50 kg of Kraton G1701M is not added, and other conditions remain unchanged.
[0035] Comparative Example 2 is based on the preparation method of Example 1, except that 2 kg of phenolic resin composition is not added, and other conditions remain unchanged.
[0036] Table 1 Contents of components and performance test table of the oil absorption swelling thermoplastic elastomer compositions of Examples 1-3 and Comparative Examples 1-2
[0037] Performance testing The oil-swellable thermoplastic elastomer compositions of Examples 1-3 and Comparative Examples 1-2 were subjected to the following performance tests. The test results are shown in Table 1.
[0038] Oil immersion test The oil-swellable thermoplastic elastomer composition is injected or molded into a 2 mm test piece, and then cut into a disc with a diameter of 12.5 mm, and the weight of the disc is A0. Soak it in IRM903 oil, 92 gasoline and 0 diesel for 24 hours, respectively, and the soaking temperature is 23°C. After being taken out and suspended for 30 minutes, the residual liquid on the surface is gently absorbed with absorbent cotton and the weight of the disc is weighed A1. Then the change rate of the disc after soaking = [(A1-A0) / A0]*100%.
[0039] Referring to Table 1, it can be seen from the comparison between Examples 1-3 and Comparative Examples 1-2 that, compared with Comparative Example 1, the mass change rates of the oil-swellable thermoplastic elastomer compositions of Examples 1-3 after immersion in IRM903 oil, 92 gasoline and 0 diesel are much higher than those of Comparative Example 1. This indicates that the addition of Kraton G1701M can effectively absorb oil substances in the external environment, thereby causing the volume of the oil-swellable thermoplastic elastomer composition to expand, which is convenient for observation.
[0040] Compared with Comparative Example 2, the appearance of the oil-swellable thermoplastic elastomer compositions of Examples 1-3 after being immersed in IRM903 oil, 92 gasoline and 0 diesel is better than that of Comparative Example 2. This indicates that after the phenolic resin composition is added, a network structure is formed with the molecular chain of the elastomer composition by physical or chemical crosslinking, so that the elastomer can still maintain a certain mechanical strength after oil absorption and avoid being dissolved.
[0041] In addition, by comparing Examples 1-3, it is found that the mass change rate of Example 2 is better than that of Example 1. The appearance of Example 3 is slightly dissolved, which may be due to the excessive amount of Kraton G1701M, which absorbs too much oil and begins to exceed the anti-dissolution ability of the elastomer composition. In general, the performance of Example 1 is the best, so Example 1 is preferred.
[0042] Embodiment 4-5 In Example 4-5, based on the preparation method of Example 1, the type of oil absorption component was adjusted, as shown in Table 2 for details.
[0043] The oil-swellable thermoplastic elastomer compositions of Examples 4-5 were subjected to the above performance tests. The test results are shown in Table 2.
[0044] Table 2 Types and performance test table of oil absorption components of Example 1 and Examples 4-5
[0045] Referring to Table 2, by comparing Example 1 with Examples 4-5, it can be seen that Kraton G1701M, Kraton G1702, and SEPTON 1020 can all be used as the oil absorption component of the present application.
[0046] Embodiment 6-8 In Examples 6-8, based on the preparation method of Example 1, the type of phenolic resin is adjusted. The specific adjustments are shown in Table 3.
[0047] The oil-swellable thermoplastic elastomer compositions of Examples 6-8 were subjected to the above performance tests. The test results are shown in Table 3.
[0048] Table 3 Types and performance test table of phenolic resins of Example 1 and Examples 6-8
[0049] Referring to Table 3, by comparing Example 1 with Examples 6-8, it can be seen that the mass change rate and appearance state of Example 1 are the best, which may be because SP1056 is a brominated heat-reactive resin. Compared with other phenolic resins, it contains more bromine components and thus has a faster vulcanization speed, making the structure of the elastomer composition more stable.
[0050] Examples 9-13 Example 12 Based on the preparation method of Example 1, 0.45 kg of stearic acid is further added to the phenolic resin composition to form a new phenolic resin composition for preparation, and the other conditions remain unchanged.
[0051] In Examples 13-16, based on the preparation method of Example 12, the amount of talcum powder added was adjusted. The specific adjustments are shown in Table 4.
[0052] The oil-swellable thermoplastic elastomer compositions of Examples 9-13 were subjected to the above performance tests, and the test results are shown in Table 4, respectively.
[0053] Table 4 Addition amount and performance test table of stearic acid in Example 1 and Examples 9-13
[0054] Referring to Table 4, it can be seen from Comparative Example 1 and Examples 9-13 that stearic acid is added to the phenolic resin composition, and stearic acid can react with zinc oxide to form a stable stearic acid zinc salt. Stearic acid zinc salt, as a kind of active substance, can further promote the carrying out of vulcanization reaction, accelerate the crosslinking between the molecular chains of the elastomer composition. By the addition of stearic acid, vulcanization reaction is more fully carried out, thereby improving the crosslinking density of the composition, which helps to enhance the physical properties of the composition and can absorb more oil substances.
[0055] As the content of stearic acid continues to increase, the content of zinc stearate continues to increase, which may form a relatively oleophobic barrier layer, hindering the penetration of oil molecules into the elastomer. Stearic acid exceeding a certain range will lead to a weakened penetration of oil into the elastomer, thereby reducing the oil absorption effect.
[0056] Examples 14-16 Example 14 Based on the preparation method of Example 1, 2 kg of the phenolic resin composition was replaced with 2 kg of a mixture of DCP and TMPTMA, the mass ratio of DCP to TMPTMA was 1:0.5, and the other conditions remained unchanged.
[0057] Example 15 Based on the preparation method of Example 1, 2 kg of the phenolic resin composition was replaced with 2 kg of a mixture of DCP and BMI, the mass ratio of DCP to BMI was 1:0.5, and the other conditions remained unchanged.
[0058] Example 16 Based on the preparation method of Example 1, 2 kg of the phenolic resin composition was replaced with 2 kg of a mixture of DCP and TAIC, the mass ratio of DCP to TAIC was 1:0.5, and the other conditions remained unchanged.
[0059] The oil-swellable thermoplastic elastomer compositions of Examples 14-16 were subjected to the above performance tests, and the test results are shown in Table 5, respectively.
[0060] Table 5 Performance test table of Example 1 and Examples 14-16
[0061] Referring to Table 5, it can be seen from the comparison between Example 1 and Examples 14-16 that DCP, no matter which of TAIC, TMPTMA, and BMI is used in combination, can effectively improve the oil absorption capacity and anti-solvent ability of the elastomer composition. In particular, when DCP and TAIC are used in combination, the effect of DCP and TAIC is better than that of DCP and the other two co-crosslinking agents. Therefore, Example 16 is preferred.
[0062] Examples 17-20 Examples 17-20 are based on the preparation method of Example 16, and the mass ratio of DCP to TAIC is adjusted. The specific adjustments are shown in Table 6.
[0063] The oil-swellable thermoplastic elastomer compositions of Examples 17-20 were subjected to the above performance tests, and the test results are shown in Table 6 respectively.
[0064] Table 6 Mass ratio of DCP and TAIC and performance test table of Example 1 and Examples 16-20
[0065] Referring to Table 6, it can be seen from the comparison between Example 1 and Examples 16-20 that as the mass ratio of DCP to TAIC continues to decrease, the mass change rate shows a trend of first increasing and then decreasing. This may be because as the mass ratio of DCP to TAIC continues to decrease, the content of TAIC continues to increase, the synergistic effect of DCP and TAIC continues to increase, and the crosslinking density of the elastomer composition continues to increase, thereby improving the oil absorption capacity of the elastomer composition. When a certain range is exceeded, the content of TAIC is too much and the content of DCP is low. At this time, DCP and TAIC have fully cooperated, and the excess TAIC is difficult to continue to increase the degree of crosslinking, but instead reduces the crosslinking density of the overall composition, thereby affecting its oil absorption capacity.
[0066] Examples 21-25 Example 21 Based on the preparation method of Example 3, in step S2, 2.5 kg of TPEE, the phenolic resin composition and the masterbatch are co-vulcanized to obtain a sulfide, and the conditions remain unchanged; In Examples 22-25, based on the preparation method of Example 21, the amount of TPEE added was adjusted. The specific adjustments are shown in Table 7.
[0067] The oil-swellable thermoplastic elastomer compositions of Examples 21-25 were subjected to the above performance tests, and the test results are shown in Table 7, respectively.
[0068] Table 7 TPEE addition amount and performance test table of Example 3 and Examples 21-25
[0069] Referring to Table 7, it can be seen from the comparison between Example 3 and Examples 21-25 that the addition of TPEE can improve the oil absorption and anti-solution ability of the oil-swelling thermoplastic elastomer composition. It may be because TPEE itself has good elasticity and flexibility, which enables it to form an effective micropore or channel structure in the composition, which is conducive to the penetration and adsorption of oils. In addition, TPEE has excellent oil resistance and good anti-solution properties for a variety of oils. After adding TPEE to the composition, the oil-solution resistance of the composition can be significantly improved. However, TPEE cannot be added too much. Due to the poor compatibility of TPEE with polypropylene, too much TPEE will reduce the oil absorption capacity of the elastomer composition.
[0070] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. An oil-swellable thermoplastic elastomer composition, characterized in that: The invention comprises the following components in parts by weight: 25 parts of EPDM rubber, 15-30 parts of polypropylene, 40-60 parts of peroxide or phenolic resin composition, 40-60 parts of oil absorption component, 0.5-2 parts of lubricant, 1-3 parts of flow regulator, and 1-2 parts of anti-aging agent; The oil absorption component includes at least one of Kraton G1701M, Kraton G1702, and SEPTON 1020; The peroxide comprises DCP and a cross-linking aid, wherein the cross-linking aid comprises at least one of TAIC, TMPTMA and BMI; the weight portion of the peroxide is 1-2 parts; The phenolic resin composition is a mixture of phenolic resin, stannous chloride and zinc oxide; the weight portion of the phenolic resin composition is 1.5-3 parts.
2. The oil-swellable thermoplastic elastomer composition according to claim 1, characterized in that: The phenolic resin includes at least one of SP1044, SP1045, SP1055, and SP1056.
3. The oil-swellable thermoplastic elastomer composition according to claim 2, characterized in that: The phenolic resin is SP1056.
4. The oil-swellable thermoplastic elastomer composition according to claim 1, characterized in that: The phenolic resin composition also includes stearic acid.
5. The oil-swellable thermoplastic elastomer composition according to claim 4, characterized in that: The mass ratio of zinc oxide to stearic acid in the phenolic resin composition is 1:1-2.
6. The oil-swellable thermoplastic elastomer composition according to claim 1, characterized in that: The peroxide is a mixture of DCP and TAIC.
7. The oil-swellable thermoplastic elastomer composition according to claim 6, characterized in that: The mass ratio of DCP to TAIC in the mixture is 1:0.3-0.
6.
8. The oil-swellable thermoplastic elastomer composition according to claim 1, characterized in that: Also includes TPEE.
9. The oil-swellable thermoplastic elastomer composition according to claim 8, characterized in that: The weight portion of the TPEE is 1.5-3 parts.
10. The method for preparing the oil-swellable thermoplastic elastomer composition according to any one of claims 1 to 7, characterized in that: The following steps are involved: The polypropylene is divided into polypropylene A and polypropylene B, and the mass ratio of the polypropylene A to the polypropylene B is 1:0.7-1.1; S1: mixing the formulated amount of polypropylene A, EPDM rubber and flow regulator uniformly and then extruding to obtain a masterbatch; S2: uniformly mixing the formulated amount of peroxide or phenolic resin composition with the masterbatch and vulcanizing the mixture to obtain a sulfide; S3: uniformly mixing the formulated amount of polypropylene B, the oil absorption component, the lubricant and the anti-aging agent, and extruding and granulating them together with the sulfide to obtain an oil absorption and swelling thermoplastic elastomer composition.
Citation Information
Patent Citations
Preparation of ultra-low hardness thermoplastic elastomer material
CN101205334A
Preparation method of low-density bulk magnetic polystyrene oil absorption material
CN104829768A
Oil absorbing expansion material as well as preparation method and application thereof
CN108219332A
Melt-blown oil-absorbing wiping cloth
CN112680880A
Oil-resistant low-pressure-change low-odor phenolic resin dynamically-vulcanized ethylene propylene diene monomer elastomer and preparation method thereof
CN115490970A